RARE-48. GROWING KNOWLEDGE AND EMERGING QUESTIONS RELATED TO POT-1 GERMLINE MUTATIONS AND ASSOCIATED MALIGNANCIES: A CASE REPORT. (11th November 2019) - Ruiz, Amber; Eastman, Boryana; Halasz, Lia; Jarvik, Gail; Brown, Lauren; Graber, Jerome
Abstract: Protection of telomeres 1 (POT1) is a member of a family of genes responsible for maintenance of telomere integrity. Germline mutations of the POT1 gene have been associated with tumorigenesis of multiple tissue types, conferring an increased risk of development of malignancies such as melanoma, chronic lymphocytic leukemia, gliomas, and cardiac sarcomas. We present the case of a 28 year old male who first presented at the age of 15 with personality changes. Several years later, he was found to have a left frontal, IDH mutated, WHO grade III anaplastic astrocytoma. Following successful treatment with gross total resection, radiation therapy, and adjuvant chemotherapy, the patient represented with an MRI showing enhancement concerning for osteomyelitis and possible tumor recurrence. Pathology of the dura was consistent with myxofibrosarcoma. Staging PET scan at that time revealed multiple hypermetabolic lung lesions found to be Lanagerhans cell histiocytosis. Given the patient's complex oncological history, genetic testing was performed. He was found to carry a heterozygous mutation of the POT1 gene. This case raises the suspicion for a broader POT1-associated cancer predisposition than previously described in the literature. Moreover, this prompts further questioning of an association between POT1 mutations and IDH status in related gliomas. Patients with POT1 mutations might also be at increased risk of secondary malignancies after radiation exposure, which may require closer observation after treatment.